Ultra-high temperature ceramic composite. (17th October 2018) - Rubio, V.; Ramanujam, P.; Binner, J.
ABSTRACT: The work carried out under the XMat research programme (Materials Systems for Extreme Environments, EPSRC Programme Grant number EP/K008749/1-2) in the field of ultra-high temperature ceramic matrix composites has been focused on the design, development and manufacture of complex shapes and large panels for use under extreme conditions. The composites are made from 2.5D woven carbon fibre preforms impregnated with HfB2 powders and with a pyrolytic carbon, PyC, matrix created using chemical vapour infiltration, CVI. More recently, the knowledge acquired during the development of these Cf-HfB2 -C composites has been focused on shortening the densification time by moving from conventional CVI to Radio Frequency-heated CVI; the work has also switched to Cf-ZrB2 -C composites. In addition, the use of 3D carbon fibre preforms has begun to be explored to improve the mechanical properties and also the replacement of PyC matrix with ZrB2 to reducing the oxidation of the composites at ultra-high temperature.